IbM PENGEMBANGAN KEPROFESIAN BERKELANJUTAN (PKB) GURU-GURU MIM WILAYAH NGAWEN DAN KLATEN UTARA BERBASIS KURIKULUM 2013 - Rahmawati, Laili Etika; Santosa, Joko; Muhroji, Muhroji (WARTA, 2015)
The society service has aimed at accompanying the teachers on understanding and conducting the program of sustainable professionalism development (PKB) based on curriculum 2013. When the society service program has finished conducted, it is expected to acquire the four goals as follow: (1) the emergence of a professional teacher group and acquire the teaching competence by implementing the active learning strategy with scientific approach based on curriculum 2013; (2) the learning devices based on curriculum 2013; (3) the research proposal is classroom action research; and (4) the scientific publication article. The method applied in the society service program was conducted with the same model as the PLPG program conducted but the program implementation was simpler or could be called as mini PLPG. The program activity was beginned by deepening of material activity which related to the concept of PKB and the concept of curriculum 2013. The concept of PKB emphasized on three points that should be developed by the teachers, they were the self development, scientific publication, and innovative work. The concept of curriculum 2013 has priority on the changing understanding of the paradigm and the basic concept of curriculum structure, the prominent were about the core and the basic competences. After the deepening materials which conducted in the first phase has finished, the activity then continued by the workshop of the learning devices which emphasized on the concept of scientific approach, the active learning, and the authentic assessment which followed by peer teaching activity. The worshop activity of learning devices was conducted by facilitating the teachers in arranging the learning scenario based on the materials determined. The peer teaching activity was conducted by divide the participants into some groups to conduct the teaching practice by turns and apply the scientific approach. The third phase was the arranging the academic writing, and it has the priority on the arranging of classroom action research (PTK). The teachers were assigned to propose the classroom action research title based on the problem emerged on their classroom. After the teachers have determined the title, the society service team divisible the job to accompany the teachers in arranging the classroom action research. The strategy used in conducting the third phase, the society servicec team acted as the consultant. By the strategies applied, it is expected that the teachers would be more directed in writing and arranging the classroom action research in order to produce the quality academic writing.